Penerapan Model Pembelajaran Cooperative Team Quiz untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI 5 SMAN 8 Denpasar pada Materi Proklamasi Kemerdekaan - Sri Datuti; Rulianto Rulianto; Yohanes Umbu Lede (Lembaga Yasin AlSys, 2025)
Numerous studies have demonstrated the effectiveness of cooperative learning models in enhancing academic achievement; however, research specifically addressing the application of the Cooperative Team Quiz (CTQ) model in high school history instruction remains relatively limited. This study aims to implement and evaluate the effectiveness of the CTQ model in improving student learning outcomes on the topic of the Proclamation of Independence. A quantitative approach was employed using a two-cycle Classroom Action Research (CAR) design. The study involved 46 eleventh-grade students (Class XI-5) from SMAN 8 Denpasar, selected through total sampling. Data were collected through learning outcome tests, student activity observations, and documentation, and analyzed using descriptive quantitative methods. The findings indicate a significant improvement in learning outcomes, with the average score increasing from 73.09 in the pre-cycle to 77.63 in Cycle I and 80.63 in Cycle II. The percentage of students achieving mastery rose from 43.48% in the pre-cycle to 80.43% in Cycle II. These results suggest that the implementation of the CTQ model effectively enhances students' active participation, strengthens group collaboration, and fosters motivation and engagement in history learning. The study concludes that the CTQ model offers a viable, innovative instructional strategy to improve both the process and outcomes of history education. The findings imply that teachers are encouraged to adopt this model as a pedagogical approach aligned with the demands of 21st-century learning. Further research is recommended to examine the model’s effectiveness across different subjects and educational levels to broaden the generalizability of the results.